Pengaruh Suhu dan Dimensi Potongan pada Pembuatan Keripik Nanas Menggunakan Penggorengan Vakum (Vacuum Frying) - Kuncoro, Sapto; Asmara, Sandi; Dharmawati, Kurnia; Tamrin, Tamrin (Jurnal Agricultural Biosystem Engineering, 2024)
Pineapple is a fruit that is generally consumed fresh by Indonesian people. The potential for pineapple fruit in Indonesia is quite good, but its utilization and marketing have not been fully implemented. Apart from that, pineapples are easily damaged so proper post-harvest handling is needed to maintain their shelf life, one of which is processing them into chips. The technology that can be used in making chips is a vacuum frying machine to maintain the appearance of color, taste, aroma and crispness in the chips produced. The research aims to determine the effect of temperature and variations in the dimensions of fruit pieces on making pineapple chips using vacuum frying. The temperature used in this research consisted of three levels including temperatures of 75, 80, and 85 ℃ and three levels of cut dimensions including dimension 1 (circle), cut dimension 2 (half circle), and cut dimension 3 (quarter circle). After conducting research and data analysis, it was found that the effect of treatment interactions on the yield value and frying time was obtained. The cut dimension factor has a significant effect on the color and crispness of pineapple chips using vacuum frying. Keywords: Cut Dimensions, Pineapple, Temperature, Vacuum Frying